1981
DOI: 10.1111/j.1469-8137.1981.tb01698.x
|View full text |Cite
|
Sign up to set email alerts
|

The Phytosociology and Ecology of Scragh Bog, Co. Westmeath

Abstract: Scragh Bog, a mire of some 23 ha, harbours plant communities representative of the more important stages in hydroseral suecession. These communities are described, classified and mapped according to Zurich-Montpellier methodology. Fen communities constitute the major part of the vegetation cover and that dominated by Sehoenus nigricans forms the basis of a new subassociation within the Cirsio-Schoenetum nigricantis Br.-Bl. et Tx. 1952. Other new syntaxa proposed are the Erico-Sphagnetum plumulosi, the Carici l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“… Location of Scragh Bog in Ireland. The site is a mesotrophic fen with a small catchment with mostly agricultural land use (O'Connell 1980, 1981). …”
Section: Methods and Locationmentioning
confidence: 99%
See 1 more Smart Citation
“… Location of Scragh Bog in Ireland. The site is a mesotrophic fen with a small catchment with mostly agricultural land use (O'Connell 1980, 1981). …”
Section: Methods and Locationmentioning
confidence: 99%
“…Scragh Bog is fed by springs near the south‐east end, by precipitation, groundwater flow and run off from the fields. The basin discharges its surplus water via a drain in the north‐western corner (O'Connell 1981). The calcium‐rich surface water originates from the springs and from diffuse groundwater inflow with a pH between 6 and 7.…”
Section: Methods and Locationmentioning
confidence: 99%
“…Similarly, it has also been shown that raised surface water levels may lead to inundations in floating fens (O'Connell, 1981;Koerselman, 1989;van Wirdum, 1991), especially on rich fens with Scorpidium species (Cusell et al, 2013b). Such rich fens are usually located at or below, instead of clearly above the water table.…”
Section: Water Table Dynamics In Floating Fens Hardly Depend On Surfamentioning
confidence: 95%
“…Cattle graze throughout the site. In county Westmeath in the central part of Ireland, northwest of Mullingar, a floating rich-fen has developed in a valley between eskers (O'Connell 1981). In the central parts of this fen a large area with S. scorpioides is found.…”
Section: Study Sitesmentioning
confidence: 99%